Reformulasi Pengelolaan Sistem Pangan Melalui Korporasi Petani Remaja di Indonesia Guna Mewujudkan Kemandirian Pangan - Lestari, Jesica; Werdiningsih, Anggun; Indil’an, Baiq Aras Sakira; Ashari, Dimas Aditya; Pratama, Rizky Dian (Primagraha Law Review, 2024)
Indonesia is a country rich in natural resource potential with agrarian potential that relies on the agricultural sector. Indeed, the agricultural sector has a large role in the development and improvement of the Indonesian economy, this can be proven by data released by the Central Statistics Agency (BPS) throughout 2019-2020 which shows that 12.72% of Gross Domestic Product (GDP) is supported by the agricultural sector. However, the current reality shows that the lack of interest of the younger generation to become farmers makes a new problem for regeneration which has an impact on the decline in agricultural commodity yields. The writing of this scientific paper uses a juridical-normative approach method with a statutory approach, a comparative, conceptual, and analytical approach that aims to analyze the urgency of the concept of food system management through farmer corporations in realizing food independence in Indonesia. The purpose of this writing is to find out and analyze the social symptoms of the community, factors that influence the low interest of youth, as well as concrete efforts to improve the quality of human resources by applying the principles of SDGs. The recommendations given in the preparation of this scientific paper are: It is necessary to formulate regulations in positive law in Indonesia regarding farmer corporations through statutory products by taking into account the reach, The direction of regulation, as well as the content that will be formed comprehensively by taking into account philosophical, sociological, and juridical aspects.